Christian political ethics - Coleman, John Aloysius, 1937- (Ethikon series in comparative ethics., 2008)
Christian Political Ethics brings together leading Christian scholars of diverse theological and ethical perspectives--Catholic, Lutheran, Calvinist, and Anabaptist--to address fundamental questions of state and civil society, international law and relations, the role of the nation, and issues of violence and its containment. Representing a unique fusion of faith-centered ethics and social science, the contributors bring into dialogue their own varying Christian understandings with a range of both secular ethical thought and other religious viewpoints from Judaism, Islam, and Confucianism. They explore divergent Christian views of state and society--and the limits of each. They grapple with the tensions that can arise within Christianity over questions of patriotism, civic duty, and loyalty to one's nation, and they examine Christian responses to pluralism and relativism, globalization, and war and peace. --From publisher's description.